2022
DOI: 10.7759/cureus.27127
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness, and Attitude in Using Dental Implants as an Option in Replacing Missing Teeth Among Dental Patients: Survey-Based Research in a Dental Teaching Hospital in Derabassi, Punjab

Abstract: BackgroundAmong many options that are available to replace missing teeth, dental implants are very popular. Information about patient awareness of dental implants is an important parameter for planning health care services and marketing. Knowledge of the treatment method minimizes any negative image that can be caused by a lack of proper communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…These results are difficult to compare with other data in the literature as they are highly dependent on the health care system, the health insurance system, and the real gross domestic product. Two other survey studies performed reported that most of patients had acceptable to good knowledge and awareness as well as a positive attitude towards using dental as a treatment option for replacing missing teeth [16,24], which agrees with the results of this current survey.…”
Section: Discussionsupporting
confidence: 92%
“…These results are difficult to compare with other data in the literature as they are highly dependent on the health care system, the health insurance system, and the real gross domestic product. Two other survey studies performed reported that most of patients had acceptable to good knowledge and awareness as well as a positive attitude towards using dental as a treatment option for replacing missing teeth [16,24], which agrees with the results of this current survey.…”
Section: Discussionsupporting
confidence: 92%
“…2017 yılında yapılan bir çalışma popülasyonunun %96,4'ü; 2022 yılında yapılan bir çalışma popülasyonunun %74,8'i dental implantlar konusunda bilgi sahibiydi. 16,17 Bu çalışmada ise katılımcıların %86,2'si eksik dişlerin rehabilite edilmesi için bir tedavi seçeneği olarak dental implantları biliyordu. Bu fark, digȇr çalışmaların farklı şehirlerde yapılması, örneklem büyüklüğü, kişilerin bilgi ve farkındalıklarının farklı yerlerde farklı zamanlarda degȋşiklik gosterebilecegȋ ile ilişkili olabilir.Günümüzde tedavinin ve ulaşılabilirliğin artmasıyla farkındalık düzeyleri değişmiş ve bireylerin farkındalığı bu sebeple artmış olabilir.…”
Section: Discussionunclassified
“…One of the major limitations of the use of dental implants from patients’ perspective, especially in low- and middle-income countries, is its high costs [ 8 , 9 ]. Furthermore, dental implants procedure is a matter of controversy in childhood and adolescence.…”
Section: Reviewmentioning
confidence: 99%